2020
DOI: 10.1186/s13046-020-01713-9
|View full text |Cite
|
Sign up to set email alerts
|

TAM family receptors in conjunction with MAPK signalling are involved in acquired resistance to PI3Kα inhibition in head and neck squamous cell carcinoma

Abstract: Background Aberrant activation of the phosphatidylinositol 3-kinase (PI3K) pathway is common in many malignancies, including head and neck squamous cell carcinoma (HNSCC). Despite pre-clinical and clinical studies, outcomes from targeting the PI3K pathway have been underwhelming and the development of drug resistance poses a significant barrier to patient treatment. In the present study, we examined mechanisms of acquired resistance to the PI3Kα inhibitor alpelisib (formerly BYL719) in HNSCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In summary, our findings highlight the likelihood that the factors governing the acquisition of resistance in HNC HPV+ may be distinct from those in HNC HPV− . While, in HNC HPV− , expression of RTKs increases following PI3K treatment [ 20 , 58 , 59 , 60 , 61 ], in HNC HPV+ , tumor cells acquire resistance to isiPI3K by the secretion of IGF2 to activate IGF1R. Our results provide the first evidence that blocking the IGF2/IGF1R pathway in combination with isiPI3K is a promising therapeutic strategy for treating HNC HPV+ patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In summary, our findings highlight the likelihood that the factors governing the acquisition of resistance in HNC HPV+ may be distinct from those in HNC HPV− . While, in HNC HPV− , expression of RTKs increases following PI3K treatment [ 20 , 58 , 59 , 60 , 61 ], in HNC HPV+ , tumor cells acquire resistance to isiPI3K by the secretion of IGF2 to activate IGF1R. Our results provide the first evidence that blocking the IGF2/IGF1R pathway in combination with isiPI3K is a promising therapeutic strategy for treating HNC HPV+ patients.…”
Section: Discussionmentioning
confidence: 78%
“…Different molecular paths can lead to isiPI3K resistance, including sustained activation of mTORC1 [ 21 , 54 , 55 ], PDK1/SGK1 [ 56 ], and MYC [ 57 ]. In HNC HPV− , acquisition of resistance to isiPI3K is driven by increased activity of receptor tyrosine kinases (RTK), like EGFR [ 20 , 58 ], AXL [ 20 , 59 , 60 ], and HER3 [ 61 ], which signal through AKT or RAS/ERK pathways, or by activation of RTKs downstream of ERK/TSC2 [ 61 ], p85 [ 62 ], and CDK4/6 [ 63 ]. While, in HNC HPV− , different mechanisms of resistance to isiPI3K have been well documented by us and by others, in HNC HPV+ , only innate resistance to isiPI3K has been reported [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, the TAM RTK family plays an important role in various cancers ( Post et al, 2021 ). Among them, AXL and MER are known proto-oncogenes and have been confirmed to be overexpressed in several cancer types ( Rothlin et al, 2014 ; Morimoto et al, 2020 ; Ruicci et al, 2020 ). While AXL and MER have been thoroughly investigated, the role of TYRO3 in cancer development remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of TYRO3 via RNAi in breast, colon, head and neck and pancreatic cancers has been reported to regulate the cellular signaling pathway by reducing the phosphorylation of STAT3, AKT, and ERK. Conversely, the overexpression of TYRO3 has been shown to increase the phosphorylation of ERK and AKT ( Lan et al, 2000 ; Ekyalongo et al, 2014 ; Duan et al, 2016 ; Qin and QIAN, 2018 ; Morimoto et al, 2020 ; Ruicci et al, 2020 ; Tsai et al, 2020 ). AKT and ERK are key mediators in regulating the survival and proliferation of cancer cells ( Herrero et al, 2015 ; Song et al, 2019 ), whereas STAT3 is a transcription factor involved in cell survival and apoptosis ( Xiong et al, 2008 ; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that persistent activation of mTOR signaling in HNSCC cell lines bearing either mutated (H1047R) or amplified PIK3CA confers resistance to alpelisib, and that the activation is mediated via AXL interaction with EGFR (57,58). Another study reported that acquired resistance to alpelisib in a PIK3CA-mutant (H1047R) HNSCC cell line was associated with increased expression of the TAM family receptors TYRO3 and AXL (59). Therefore, as with many other targeted therapies, dissecting the underlying mechanisms driving resistance may lead to improved treatment approaches.…”
Section: Methodsmentioning
confidence: 96%